Local dynamics of worker activity of the invasive Vespula germanica and V. vulgaris (Hymenoptera: Vespidae) wasps in Argentina - Masciocchi, Maite; Pereira, Ana Julia; Corley, Juan Carlos (2017)
1. The abundance of insects depends essentially on the reproductive success of individuals. In social insects, however, the abundance of sterile workers outside a nest depends on colony size but is also determined by ontogeny, nest demands, and local environmental factors. For invasive social wasps, the drivers of worker abundance are important because they determine the impact that these species have on the native systems, people, and their goods. 2. The aim of the present study was to understand the relative importance of endogenous and exogenous factors on the abundance of workers of populations of Vespula spp., by analysing 12 years of trap captures in NW Patagonia. This is the first attempt to model the activity levels of invasive Vespula spp. wasps over time in Argentina. 3. It was shown that between years, the worker activity of both vespids presents fluctuations, and that of V. germanica is determined by the spring mean temperatures. Within the flight season, V. germanica worker activity is affected by the relative abundance of workers in that year, whereas for V. vulgaris, activity it is affected by the relative abundance of both species that year. We found no relationship between individual weather variables and activity within a flight season for both wasps. 4. The patterns observed for Argentina are similar to those observed in all invaded temperate areas where Vespula spp. are established. This study provides useful information to understand the driving factors that affect Vespula spp. worker activity in Argentina. This could be a necessary step to develop plans to manage these invasive social insects.